2004
DOI: 10.1038/labinvest.3700026
|View full text |Cite
|
Sign up to set email alerts
|

Low O2 and high CO2 in LLC-PK1 cells culture mimics renal ischemia-induced apoptosis

Abstract: Ischemia, absence or loss of blood flow in organs always presents as a dual phenomenon: tissue oxygen deficit and CO 2 excess (hypercapnia). Commonly hypoxic cell culture models kept CO 2 at normal nonischemic values. We report a study of apoptosis in an in vitro model of renal hypoxia that mimics in vivo tissue gas atmosphere composition determined during experimental ischemia in rat kidney (low O 2 plus high CO 2 ). Renal tubular LLC-PK1 cell were transiently exposed to hypoxia, to hypercapnia or to both con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Previous studies revealed that hypoxia induces death of tubular epithelial cells via apoptosis (29,30). Interestingly, the viability of cells cultured in 2% O 2 for 72 h normalized to the viability of cells cultured under normal conditions was significantly reduced in cells overexpressing Dragon (Dra#4 and Dra#10) compared with control cells (Ctrl#2 and Ctrl#6; Fig.…”
Section: Dragon Increased Hypoxia-induced Cell Death In Imcd3mentioning
confidence: 67%
“…Previous studies revealed that hypoxia induces death of tubular epithelial cells via apoptosis (29,30). Interestingly, the viability of cells cultured in 2% O 2 for 72 h normalized to the viability of cells cultured under normal conditions was significantly reduced in cells overexpressing Dragon (Dra#4 and Dra#10) compared with control cells (Ctrl#2 and Ctrl#6; Fig.…”
Section: Dragon Increased Hypoxia-induced Cell Death In Imcd3mentioning
confidence: 67%
“…5 Here we report that the CDK inhibitors roscovitine 6 and TAT-NBI1 7,8 provide protection against cell death in a well-established ischemia/reperfusion (I/R) model in porcine renal tubular cells (LLC-PK1). 9 When analyzing the molecular mechanism, we found the protective effect required of CDK5. CDK5 is an atypical member of the CDK family 10,11 that is highly conserved in mammals and is expressed in all tissues, although the highest expression levels are observed in the central nervous system.…”
Section: Introductionmentioning
confidence: 92%
“…7,8 The cellular model we used was the I/R model developed from an epithelial cell line deriving from pig kidney proximal tubule cells (LLC-PK1). 9 In this cell model, cells are subjected to hypoxia (1% O 2 ) and hypercapnia (18% CO 2 ) for 24 h, and Ischemia reperfusion processes induce damage in renal tubules and compromise the viability of kidney transplants. Understanding the molecular events responsible for tubule damage and recovery would help to develop new strategies for organ preservation.…”
Section: Cdk Inhibitors Increase Cell Viability In An Ischemia/reperfmentioning
confidence: 99%
“…Hypoxia is maintained by clamping and incubating the chambers at 37°C for the requested period. The composition of the gas mixture may vary depending on the bicarbonate content of the culture medium and the required level of acidity change (pH level), since hypercapnia can mimic the rapid development of acidic pH of ischemic tissues [11]. The CO 2 content is typically between 5 and 20% with 80-95% N 2 .…”
Section: Hypoxia-reoxygenation Inductionmentioning
confidence: 99%